The Development of Islamic Spirituality in Indonesia - Sri Mulyati (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2014)
This writing describes the growth of Islamic spirituality in Indonesia and, in short, the position of Mysticism in Islamic teachings, with its objectives and its part in the current Islamic religious movements, as well its social, cultural, educational and political roles in Islamic society. It also views the challenge and its future in Indonesia. The progress achieved by sufi until now is considered, as well its weaknesses as its strengths, and comparing this with the situation outside the country, and assuming that in the case of Indonesia, such weaknesses and strengths might be relatively the same. Furthermore, the paper displays the example of one particular sufi order that still plays an important role in Indonesia, namely the Tarīqa Qādiriyya wa Naqshbandiyya in West Java. In addition, considering the current religious climate in the country, we may perhaps draw some conclusions as to prospects for sufi in Indonesia.